2000
DOI: 10.1159/000006997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brain Natriuretic Peptide in the Diagnosis of Heart Failure

Abstract: A diagnosis of heart failure (HF) can be difficult, especially in patients with mild symptomatology. The purpose of this study was to evaluate the significance of brain natriuretic peptide (BNP) in the diagnosis of HF with systolic or isolated diastolic ventricular dysfunction. One hundred patients and 9 controls were included in the study. Eighty-five patients were diagnosed with HF, based on clinical and echocardiographic findings. BNP levels were accurate for the diagnosis of HF, with an area under the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…The mean (SE) BNP level was significantly increased in both the DHF (56 [30] pg/mL) and the SHF (154 [28] pg/mL) groups compared with controls (3 [38] pg/mL) (P = .02 and .001, respectively). The mean ANP level was also significantly increased in both the DHF and the SHF groups (34 [39] and 92 [98] pg/mL, respectively) compared with controls (14 [10] pg/mL) (P=.02 and .001, respectively). Both natriuretic peptides were increased significantly more in the SHF group than in the DHF group.…”
Section: Patient Characteristicsmentioning
confidence: 96%
“…The mean (SE) BNP level was significantly increased in both the DHF (56 [30] pg/mL) and the SHF (154 [28] pg/mL) groups compared with controls (3 [38] pg/mL) (P = .02 and .001, respectively). The mean ANP level was also significantly increased in both the DHF and the SHF groups (34 [39] and 92 [98] pg/mL, respectively) compared with controls (14 [10] pg/mL) (P=.02 and .001, respectively). Both natriuretic peptides were increased significantly more in the SHF group than in the DHF group.…”
Section: Patient Characteristicsmentioning
confidence: 96%
“…These authors found that, among the natriuretic peptides evaluated, BNP was the most accurate for the diagnosis of HF (accuracy of 96%). We evaluated the value of BNP in the diagnosis of HF in patients with mild to moderate symptoms (7). The accuracy of BNP for the diagnosis of HF, either with systolic or diastolic dysfunction, measured by the area under the ROC curve, was 92%.…”
Section: Bnp In the Diagnosis Of Hf And Asymptomatic Left Ventricularmentioning
confidence: 99%
“…Furthermore, the plasma BNP level is felt by some to be the most single accurate predictor of the presence or absence of congestive heart failure. Therefore, the BNP may be a more sensitive and specific indicator of ventricular disorders [2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%